2016
DOI: 10.1038/nrdp.2016.88
|View full text |Cite
|
Sign up to set email alerts
|

Hookworm infection

Abstract: Hookworms are soil-transmitted nematode parasites that can reside for many years in the small intestine of their human hosts; Necator americanus is the predominant infecting species. Adult worms feed on the blood of a host and can cause iron deficiency anaemia, especially in high-risk populations (children and women of childbearing age). Almost 500 million people in developing tropical countries are infected, and simulation models estimate that hookworm infection is responsible for >4 million disability-adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
233
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(247 citation statements)
references
References 193 publications
(246 reference statements)
3
233
0
11
Order By: Relevance
“…It is important to note that the strain of mouse used for most of these studies has been C57BI/6 mice, which has a nonfunctional allele of Nramp1, a divalent metal (iron and manganese) transporter that renders them more susceptible to infections (Canonne-Hergaux et al, 1999; Fritsche et al, 2012; Loomis et al, 2014; Powell and Frelinger, 2017; Soe-Lin et al, 2009). In humans, clinical data support our findings that dietary iron supplementation provides beneficial outcomes, especially in developing countries where low iron status may be prevalent (Loukas et al, 2016; Mwangi et al, 2017; Oppenheimer, 1989, 1998, 2001). However in malaria endemic areas, iron supplementation was associated with a negative outcome for patients (Clark et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…It is important to note that the strain of mouse used for most of these studies has been C57BI/6 mice, which has a nonfunctional allele of Nramp1, a divalent metal (iron and manganese) transporter that renders them more susceptible to infections (Canonne-Hergaux et al, 1999; Fritsche et al, 2012; Loomis et al, 2014; Powell and Frelinger, 2017; Soe-Lin et al, 2009). In humans, clinical data support our findings that dietary iron supplementation provides beneficial outcomes, especially in developing countries where low iron status may be prevalent (Loukas et al, 2016; Mwangi et al, 2017; Oppenheimer, 1989, 1998, 2001). However in malaria endemic areas, iron supplementation was associated with a negative outcome for patients (Clark et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Regulatory T cell (Treg) development is also stimulated during hookworm infection (11) that enhances the cloaking effect through the release of the regulatory cytokines IL-10 and transforming growth factor (TGF) ÎČ (12). In addition, hookworms induce activation of parasite-specific and total immunoglobulin E (IgE) and the mobilization of the innate immune systems including mast cells, eosinophils, and basophils (13). Indeed, a recent large-scale community deworming study showed that helminths actively decrease immune responsiveness and modulate immune checkpoint expression in infected individuals (14).…”
Section: Ancient Cloakersmentioning
confidence: 99%
“…Much of our current understanding comes from wild rodent parasites that have been adopted for laboratory use, including Heligmosomoides polygyrus, 10 Nippostrongylus brasiliensis, 11 Trichinella spiralis, 12 and Trichuris muris, 13 that closely mimic human helminth infections. Although the life cycles of these nematodes vary greatly, a crucial part of their lifespans is spent in the intestinal tract where a distinct form of protective immunity is elicited, namely type 2 immunity.…”
Section: Helminths and Humansmentioning
confidence: 99%